Knowledge, Attitudes and Practices of Animal Bite Victims Attending an Anti-rabies Health Center in Jimma Town, Ethiopia. - Tadele Kabeta; Benti Deresa; Worku Tigre; Michael P Ward; Siobhan M Mor (Public Library of Science (PLoS), 2015)
Background Rabies is an important but preventable cause of death in Ethiopia. We assessed the knowledge, attitudes and practices of animal bite victims attending an anti-rabies health center in Jimma Town, Ethiopia. Methodology/principal findings Between July 2012 and March 2013 a cross-sectional questionnaire was administered to 384 bite victims or their guardians in the case of minors (aged <15 years). Factors associated with knowledge, attitudes and practices were evaluated using generalized linear models. Almost all participants (99%) were aware that rabies was transmitted by the bite or lick of a rabid dog, however only 20.1% identified "germs" as the cause of disease. A majority of participants stated rabies could be prevented by avoiding dog bites (64.6%) and confining dogs (53.9%); fewer (41.7%) recognized vaccination of dogs/cats as an important preventive strategy. Regarding attitudes, most (91.1%) agreed that medical evaluation should be sought as soon as possible. However, most (75.0%) also believed that traditional healers could cure rabies. Rural residence (adjusted odds ratio [OR] = 2.1, p = 0.015) and Protestant religion (OR = 2.4, p = 0.041) were independently associated with this belief. Among 186 participants who owned dogs, only 9 (4.8%) had ever vaccinated their dog and more than 90% of respondents indicated that their dog was free-roaming or cohabitated with the family. Only 7.0% of participants applied correct first aid following exposure, and the majority (47.7%) reported that the animal was killed by the community following the incident. Female sex and Muslim religion were independently associated with higher and lower practices scores, respectively, due largely to differences in animal management practices following the incident. Conclusions/significance Although respondents demonstrated reasonably sound knowledge of rabies and its transmission, attitudes and practices were inconsistent with rabies prevention. Culturally- and gender-sensitive activities that promote proper first aid and healthcare seeking behavior as well as appropriate animal management, particularly in rural areas, are needed to prevent deaths associated with rabies in this setting.